Nilai-Nilai Penderitaan: Sebuah Kajian Teologis tentang Fungsi Penderitaan dalam Hidup Orang Percaya: Sebuah Kajian Teologis tentang Fungsi Penderitaan dalam Hidup Orang Percaya - Budiyono, Budiyono (Jurnal Kala Nea, 2023)
Suffering is an unpleasant condition of life. Suffering is synonymous with bad conditions in life, call it sickness, deprivation, distress, and struggle, persecution, discrimination and so on. However, in the Christian faith it is also a part of the believer's life, because suffering is also one of his life calls from God.  Christians are not only called by God to believe, be faithful, be saved, witness, serve and so on, but suffering together with Christ becomes one of God's callings as well.  Behind suffering there are spiritual values contained in it, which of course God has a special purpose for the life of faith of believers before God. This study will theologically discuss how the values of suffering and how the function of suffering is for the life of believers, as well as how its implications for the life of believers in Indonesia.